THE POLYGAMY ESSENCE ACCORDING TO QURAISH SHIHAB “Reject prejudice, eliminate confusion” - Syahrin, Alfi (Universitas Islam Negeri Raden Fatah Palembang, 2021)
This journal discussed Quraish Shihab's thoughts about the true essence of polygamy, where Quraish Shihab considers that many groups who misinterpreted and misunderstand polygamy so that he pours his thoughts on polygamy in neutral glasses, it means he is not supporting or rejecting polygamy. By using Descriptive-qualitative approach, the researcher can describe the characteristics of the population or a phenomena in his research to measure the phenomenon of a reality with ideal parameters, in other words the reality of polygamy that occurs in a society is measured by polygamy theories in accordance with Islamic shari'a. Quraish Shihab explained in detail about the meaning, caused, requisite, and also offers the criteria of women who can be polygamous so it can being concluded that polygamy is an emergency door in the aircraft that can be opened during emergencies and follow the interruption of the aircraft crew, this door should not be closed nor should it will be opened under normal circumstances.